Wind load assessment with the JPDF of wind speed and direction based on SHM data. (January 2023) - Ding, Yang; Ye, Xiao-Wei; Guo, Yong
Abstract: The calculation of basic wind speed (wind load) in return period is directly related to the wind resistance design of long-span bridge, high-rise building and etc. Nowadays, the calculation of basic wind speed in Chinese codes (GB50009-2012) mainly depends on the probability distribution function (PDF) of extreme wind speed, that is, univariate Gumbel PDF. However, this method doesn't consider the influence of wind direction and the finite mixture (FM) of Gumbel PDF. In this paper, we use the Angular-linear (AL) model to characterize the extreme wind speed and wind direction, that is, joint PDF (JPDF). Specially, the FM Gumbel PDF is used to model the extreme wind speed and FM von Mises PDF is used to model the wind direction based on structural health monitoring (SHM) data. Then, the Genetic algorithm (GA) method is applied to solve the multi parameter solution in FM-AL model. Finally, the results of basic wind speed with return period of 100 years are compared based on the univariate Gumbel PDF (GB50009-2012 of Chinese code), FM Gumbel distribution, univariate Gumbel distribution + FM von Mises distribution and FM Gumbel distribution + FM von Mises distribution.